Indole: an evolutionarily conserved influencer of behaviour across kingdoms - Tomberlin, J; Crippen, T; Wu, G; Griffin, A; Wood, T; Kilner, R (John Wiley & Sons Australia, Ltd, 2016)
Indole is a key environmental cue that is used by many organisms. Based on its biochemistry, we suggest indole is used so universally, and by such different organisms, because it derives from the metabolism of tryptophan, a resource essential for many species yet rare in nature. These properties make it a valuable, environmental cue for resources almost universally important for promoting fitness. We then describe how indole is used to coordinate actions within organisms, to influence the behavior of conspecifics and can even be used to change the behavior of species that belong to other kingdoms. Drawing on the evolutionary framework that has been developed for understanding animal communication, we show how this is diversely achieved by indole acting as a cue, a manipulative signal, and an honest signal, as well as how indole can be used synergistically to amplify information conveyed by other molecules. Clarifying these distinct functions of indole identifies patterns that transcend different kingdoms of organisms.